Needs analysis for the development of a digital addiction awareness program at the middle school level - Tokatlı, Dilek; Acar Erdol, Tuba (Journal of Dependence, 2025)
Objective: This study aims to determine the educational needs of middle school students regarding a Digital Addiction Awareness Program. Method: A mixed-methods research design was employed. The quantitative part followed a survey model, while the qualitative part was structured as a case study. The study group consisted of 292 middle school students for the quantitative phase and 16 participants (8 school counselors and 8 academic experts in digital addiction) for the qualitative phase. Data collection tools included a Personal Information Form, the Digital Addiction Scale for Children, and a SemiStructured Interview Form. Quantitative data were analyzed using descriptive statistics, while qualitative data were examined through descriptive analysis. Results: The most commonly used digital devices among students were mobile phones, followed by TVs, information technology devices, and gaming consoles. It was found that 24.3% of participants did not use digital devices daily, 57.2% used them for one hour, 14.7% for two hours, and 3.8% for three hours per day. Students’ level of risky digital device usage was determined to be low. Based on the results, a proposed training program was developed, consisting of six themes, including learning objectives, content, teaching methods, and assessment strategies. Conclusion: In light of the findings, it is recommended that a Digital Addiction Awareness Program be developed and implemented, starting with eighth-grade students and extending to other middle school levels.